Applications of real-time chemical stratigraphy in support of the safe drilling of HPHT wells: examples from the Shearwater Field, Central North Sea, UK. Issue 1 (2019) - Atkin, Daniel; Vieira, Manuel; Taylor, Ben
No abstract available